2007
DOI: 10.1021/jf0620867
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Aroma Compound Transfer from a Solid and Complex-Flavored Food Matrix Packed in Treated Papers or Plastic Packaging Film

Abstract: The objective of this work was to study the transfer of four aroma compounds (ethyl butyrate, ethyl hexanoate, cis-3-hexenol, and benzaldehyde) from a solid and complex-flavored food matrix (sponge cake) toward and through packaging films placed in indirect contact during storage in accelerated aging conditions (38 degrees C and 86% relative humidity gradient). The efficiency of treated papers relative to that of standard paper and plastic as barrier was tested. Before storage, aroma compound volatility in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Those four aroma compounds were used to characterize the physicochemistry of aroma compound transfer through packaging. 18 headspace was SPME-extracted and analysed by D-GC-O by trained assessors who rated the odour similarity of this extract with one obtained from glass packaging stored under the same conditions. The higher the score, the higher was the odour similarity between the tested and the glass packaging extracts.…”
Section: Retention Of Aroma Compounds In the Flavoured Sponge Cake Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Those four aroma compounds were used to characterize the physicochemistry of aroma compound transfer through packaging. 18 headspace was SPME-extracted and analysed by D-GC-O by trained assessors who rated the odour similarity of this extract with one obtained from glass packaging stored under the same conditions. The higher the score, the higher was the odour similarity between the tested and the glass packaging extracts.…”
Section: Retention Of Aroma Compounds In the Flavoured Sponge Cake Afmentioning
confidence: 99%
“…The objective of this work was to use D-GC-O to compare the global odour of a solid food matrix flavoured before baking with either a 'viennoiserie' aromatic note, complex but little concentrated, or with a simplified but more concentrated mixture of aroma compounds used for physicochemical studies, 18 then stored in a glass packaging or in pouches made with treated papers or with plastic packaging, in accelerated transfer conditions (high temperature and relative humidity gradient). Identifications of aroma compounds by GC-mass spectrometry (GC-MS) and determination of their retention in the sponge cake were made before and after storage to explain the D-GC-O results.…”
Section: Introductionmentioning
confidence: 99%
“…Flavors play important roles in food deterioration and consumer satisfaction . The loss of flavors during food processing and storage was detrimental to food organoleptic quality and shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…Flavors play important roles in food deterioration and consumer satisfaction. 1 The loss of flavors during food processing and storage was detrimental to food organoleptic quality and shelf life. Starch was chosen as biodegradable food packaging materials for its wide botanical source, economic price and totally biodegradable ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…also studied the permeability of a mixture of aroma compounds in a food model into paper and BOPP films using the quasi‐isostatic method (i.e. exposing a film to one side of known constant concentration of permeant and accumulating the permeated compound on the other side values below 5% of the constant concentration side) and found that the P of aroma compounds was higher in BOPP than in the paper . Furthermore, Nerín et al .…”
Section: Introductionmentioning
confidence: 99%